Thickness dependence of crystalline structure of Al-doped ZnO thin films deposited by spray pyrolysis - Garces Pineda, Felipe Andres (2015)
In this work, we have investigated the influence of thickness on crystalline structure of Al-doped ZnO films. Transparent conducting oxide films were grown by the spray pyrolysis technique from precursors prepared via the sol-gel method. We determined the structural properties of the films by performing X-ray diffraction and mosaicity measurements, which evidenced an increase of disorder and inhomogeneity between crystalline domains as the films thickened. This behavior was attributed to plastic deformation of the films as their thickness increased. Disorder is usually caused by internal stress in the crystalline structure of the film, which is due to diverse factors such as lattice and thermal mismatches between substrate and sample, postdeposition heat treatments, film growth parameters, film thickness, etc. Although there are several reports concerning stress-induced optical and electrical fluctuations of ZnO films, due to annealing or deposition processes, different substrates types and doping, the thickness dependence of structural characteristics is scarcely reported.